Social and Economic Impact Due to Ageing and Climate Change in Sultan Abu Bakar Dam, Cameron Highlands Hydropower Scheme - Sidek L.B.; Basri H.; Rasip N.F.N.B.M.; Syasya A.; Derus N.A.; Ahmad S.A.; Hassan S.A.; Din N.M. (Springer Science and Business Media Deutschland GmbH, 2024)
The ageing of dams and climate change are inevitable. These natural occurrences represent a substantial natural hazard that may negatively affect the community and economy close to the dam in both direct and indirect ways. Our society is currently concerned about climate change, as its effects are becoming more universally recognized. Large facilities like dams, which may be at risk from climate change along with areas and populations, must be resilient to its impacts. This research assesses the socioeconomic and financial impacts of ageing and climate change at the Sultan Abu Bakar Dam, a hydropower project in Cameron Highlands. It quantifies the number of People at Risk (PAR), the Loss of Life (LOL), and the cost of the economic consequences byusing theextracted points of interest (POI). Landuse in the Pahang state is obtained from the Kertau Rectified Skew Orthomorphic (RSO) Malaya land map produced by the Jabatan Ukur dan Pemetaan Malaysia (JUPEM). The People at Risk (PAR), Loss of Life (LOL) and the economic damages are calculated based on the Geographic Information System (GIS). The cost of economic consequences is calculated by houses, agriculture, commercial, public facilities and infrastructures and utilities area. According to the results, the PMF scenario will have the greatest social consequences with a PAR value of 231 individuals, while the CDF scenario is with a PAR of 56 individuals. In the case where the Sultan Abu Bakar Dam is affected by a dam breakage incident, the damages will cost the most for the PMF scenario than the CDF scenario. Based on this research, the constant changing of climate change and the ageing of dams can be seen as a crucial matter and studies of reducing its impact on the people surrounding the dam area should be constantly updated to reduce the number of lives lost due to dam failures. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.